The Role of Principal Leadership in Vocational Schools Panca Sakti Makassar - Saggaf, M. Said; Wahyuddin, Baso Asrul; Akib, Haedar; Nasrullah, Muh (Jurnal Office, 2018)
This study aims to study the description of the leadership of school principals in Panca Sakti Vocational School Makassar. This study uses quantitative research with 36 teachers from Makassar Panca Sakti Vocational School. Data collection uses collection techniques, questionnaires, interviews and collection while the data analysis technique used is percentage. The results of this study show how the role of the principal of the Panca Sakti Makassar Vocational School is categorized as good with a percentage of 82.7 percent. This can be seen from various indicators regarding the leadership of school principals where they were asked as executors to be well approved with a percentage of 82.02 percent, as planners expressed as good with a percentage of 84.22 percent, as supervisors categorized as good at 81.3 percent, acting as supporters of rewards / praise and sentences were stated to be quite good with a percentage of 75.7 percent, acting as a referee and claimants were declared good with a percentage of 88 percent, and holders of responsibility for group members were categorized as good with a percentage of 88.61 percent.